THE DEPENDENCE OF THE SUCCESS RATE OF ALPHA-TRAINING ON EXTRAVERSION AND NEUROTICISM - B. V. Chernyshev; Ye. S. Osokina; N. V. Ilyushina; M. S. Trunova; Ye. G. Chernysheva (Бюллетень сибирской медицины, 2013)
The present paper shows the relationship of the success rate of alpha-training – learning to voluntarily increase the power of the alpha-rhythm with the help of the neurofeedback – with factors of the "Big Five" model of personality traits (NEO–FFI). It was found that most successful at the task of training were the subjects with low scores on Extraversion dimension and moderately high scores on Neuroticism dimension.